Bacterial Identification and Drug Susceptibility Patterns in Pregnant and Non Pregnant UTI Patients - Fatima, Syeda Sograh (SpringerBriefs in Forensic and Medical Bioinformatics,, 2018)
This book provides a review of essential research on urinary tract infections (UTIs), as well as a broader perspective on methodologies adopted for the isolation and identification of the bacteria from urine samples of pregnant and non-pregnant women on the basis of their cultural, morphological and biochemical characteristics. The identification is extended to the strain level by means of molecular identification involving BLAST as a bioinformatics tool. The book also addresses the roles of various other bioinformatics tools for tracing the phylogenetic tree and conservation studies among the bacteriocin of the identified bacteria. Lastly, it assesses the antibiotics resistance patterns of these isolates.